Analysis of the 10th Grade Nahwu Sharaf Textbook Based on Rusydi Ahmad Thu’aimah’s Perspective - Ramadhani, Nida Husnia; Mulyani, Rinda Eka; Muhaiban, Muhaiban (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the content of the 10th grade Nahwu Sharaf book published by KSKK Kemenag in 2020 with the analysis of Rusydi Ahmad Thu'aimah as an Arabic language learning expert. Nahwu sharaf is Arabic grammar lessons which include morphology and syntax. Content analysis includes 4 aspects, namely analysis of book content, material preparation, material presentation, and book output display. The research method used is Krippendorff's content analysis method with a qualitative approach. The research step consists of unitizing, the researcher determines the unit of analysis in the form of phrases, namely book analysis and the perspective of Rusydi Ahmad Thu'aimah. The next step is sampling, namely the entire contents of the book. Third is coding, called coding because in this process researchers group data based on research categories including book content, material structuring, material presentation, and output in the form of printed books. Fourth is reducing by selecting data to find important data only. Next is inferring, which is drawing conclusions by connecting the data findings. The last is narrating or compiling a research report. Findings reveal that the textbook aligns well with the curriculum and employs an inductive approach which makes it easier to deepen the grammar material, but it has weaknesses such limited illustrative visuals and gradation of materials. The study concludes that This textbook has good quality in presenting the material but needs to improve several supporting aspects as mentioned. This research can contribute to improving the quality of textbooks in the future.